A simplified continuum damage mechanics based modeling strategy for cumulative fatigue damage assessment of metallic bolted joints. (February 2020) - Liu, Ning; Cui, Xiaodong; Xiao, Jian; Lua, Jim; Phan, Nam
Highlights: We developed cumulative fatigue damage modeling approach for metallic bolted joints. Continuum damage mechanics based critical plane method was proposed. A cycle jumping algorithm with a fixed damage evolution rate is adopted. A simplified modeling strategy that only depends on the maximum stress states. Our approach is applicable to non-proportional multiaxial loading conditions. Abstract: Fatigue damage and consequent failure account for the majority of the failure in metallic bolted joints of aerospace and mechanical engineering applications. In this paper, we present a cumulative fatigue damage evaluation approach for metallic bolted joints based on a combined continuum damage mechanics (CDM) theory and the critical plane approach. The analysis approach is applicable to both proportional and non-proportional multiaxial loading conditions. A cycle jumping based algorithm with a fixed damage evolution rate is adopted for efficient numerical approximation. To further increase the computational efficiency, a simplified modeling strategy is developed to avoid the expensive calculation of the full loading-unloading cyclic stress history. The proposed approach is established based on the assumption that a linear relation can be established between the minimum and maximum stress tensors in high-cycle fatigue analysis and is thus only dependent on the maximum stress states. A set of examples including a notched specimen and a metallic bolted joint with pre-tension are simulated to demonstrate the simplified approach.